2012
DOI: 10.1159/000336864
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Changes in Cognitive Functioning in the Elderly: Age- and Education-Specific Reliable Change Indices for the SIDAM

Abstract: Background/Aims: The diagnostic criteria for dementia include reliable evidence of cognitive deterioration over time measured by cognitive tests. The Structured Interview for the Diagnosis of Dementia of the Alzheimer Type, Multi-infarct Dementia and Dementia of other Etiology according to DSM-III-R, DSM-IV and ICD-10 (SIDAM) is a neuropsychological instrument to determine cognitive status in patients with mild cognitive impairment (MCI) and dementia. Normative data for changes in cognitive functioning that no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 72 publications
0
8
0
2
Order By: Relevance
“…Indeed, in the current study, there are large educational differences between age bands (e.g., 16–43% of individuals in the oldest-old age bands, where the proportion of women is higher, with less than high school education compared to 3–10% of young-old individuals, where the proportion of women to men is nearly equivalent, with less than high school education), although the interaction reported was not a result of educational differences. Other studies of cognition in the extremely elderly have not found an effect of gender (Coluccia, Gamboz, & Brandimonte, 2011; Davey et al, 2013; Stein et al, 2012). The lack of other effect modifications by gender in the present study is consistent with literature suggesting that gender may not be the most significant contributor to cognition among the oldest-old, though additional evidence about the specific nature of the interaction on these measures is a subject for future study.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Indeed, in the current study, there are large educational differences between age bands (e.g., 16–43% of individuals in the oldest-old age bands, where the proportion of women is higher, with less than high school education compared to 3–10% of young-old individuals, where the proportion of women to men is nearly equivalent, with less than high school education), although the interaction reported was not a result of educational differences. Other studies of cognition in the extremely elderly have not found an effect of gender (Coluccia, Gamboz, & Brandimonte, 2011; Davey et al, 2013; Stein et al, 2012). The lack of other effect modifications by gender in the present study is consistent with literature suggesting that gender may not be the most significant contributor to cognition among the oldest-old, though additional evidence about the specific nature of the interaction on these measures is a subject for future study.…”
Section: Discussionmentioning
confidence: 74%
“…In a sample of HIV+ and HIV− women, Manly and coauthors (2011) found that reading level as defined by the WRAT-III had the strongest relationship to cognitive performance, compared to HIV status, education, and in some cases, age (Manly et al, 2011). However, the majority of studies of cognition in the oldest-old do use education as a marker for premorbid ability and it is often found to be a significant predictor of cognitive performance (Beeri et al, 2006; Coluccia et al, 2011; Davey et al, 2010; Dore et al, 2007; Kenny et al, 2013; Miller et al, 2010; Stein et al, 2012; Welsh-Bohmer et al, 2009), though a study of verbal fluency performance in elderly individuals found no significant differences based on reading ability or education (Ravdin et al, 2003). We do provide age- and education-based normative data in the supplementary materials as we know that clinicians more often have access to years of education than WRAT Reading performance.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent analyses will also compare the multiwave approach with other methods of evaluating cognitive change such as a reliable change index approach (e.g., Stein et al, 2012) [55] and analysis of whether practice effects in early waves predict subsequent aMCI status in ways similar to other studies (e.g., Duff et al, 2008) [56] It will also be critical to compare biomarker profiles for the aMCI robust-multiwave vs. cognitively healthy groups and to continue longitudinal follow-up to further assess cognitive trajectories and to establish dementia endpoints. The validity of the current multiwave aMCI classification will be supported if the aMCI group shows neuroimaging and/or CSF profiles consistent with preclinical AD, and ultimately, higher rates of AD.…”
Section: Discussionmentioning
confidence: 99%
“…The main instruments used to assess cognitive functions were the Structured Interview for the Diagnosis of Dementia of the Alzheimer Type, Multi-infarct Dementia and Dementia of other Etiology according to DSM-III-R, DSM-IV and ICD-10 (SIDAM), the Mini-Mental State Examination (MMSE), and the CERAD-NP battery. Within this study, RCI scores were calculated for all three instruments [53,54,55]. The RCI scores were adjusted for the sociodemographic variables of age, gender, and education as these variables showed a significant impact on cognitive test performance.…”
Section: Resultsmentioning
confidence: 99%